Pengaruh Variasi Berat Filler Karbon Aktif Tempurung Kelapa Terhadap Struktur Dan Kekuatan Tarik Komposit - Putra, Fredy Gusttina, Ir.Ngafwan, MT, Tri Widodo Besar Riyadi. ST. MSc. Ph.D (2016)
This study aimed at describing the influence of mass of carbon filler obtained from coconut shell activated on the structure and mechanical properties of carbon-polyester composites. The composition of the composite was varied using weight fraction with 1%, 3% and 6%, while polyester resin was made by Yukalac 157 BQTN - EX. The carbon articles was mixwed with resin using stirring methods with a maximum rotation speed of 2.200 rpm for 10 minutes. The test specimen was conducted using a standard tensile pull test of ASTM D 638-01. Prior to tensile test, the crophoto of the specimen was taken in order to determine the omposition of the carbon particles in the composite. The result showed that the average distance of the carbon particles in the composite contained 1%, 3% and 6% carbon was 53.32 μm, 39.21 μm and 33.78 μm, respectively whereas the diameter of the carbon was in the range of 12.65 μm to 26.27 μm. The structue of the compposite showed that the higher the weight fraction of carbon, the more tightly the carbon particles are. The tensile test showed that the tensile strength (yield) of the composite with 0%, 1%, 3% and 6% carbon active produced 34.19, 33.31, 29.41 and 28,4 N/mm2, respectively. The maximum strain of the composite for 0%, 1%, 3% and 6% carbon active produced 0.95%, 1.24%, 1.13% and 1.19%. Although the tensile strength of the activated carbon composite is lower than the composite polyester,the particles of activated carbon can increase the strain of the composite.